2020
DOI: 10.3164/jcbn.20-38
|View full text |Cite
|
Sign up to set email alerts
|

Cacao polyphenols regulate the circadian clock gene expression and through glucagon-like peptide-1 secretion

Abstract: Energy metabolism and circadian rhythms are closely related together, i.e., the timing of nutrient intake affects metabolism under the regulation of circadian rhythms. Previously, we have reported that cacao liquor procyanidin (CLPr) promotes energy metabolism, resulting in preventing obesity and hyperglycemia. However, it is not unclear whether CLPr regulates clock gene expression. In this study, we investigated whether the administration timing of CLPr affected clock gene expression and found that CLPr regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
(62 reference statements)
1
5
0
Order By: Relevance
“…Recently, we have demonstrated that a single oral administration of CLPr at ZT3 also increased phosphorylation of AMPK and LKB1 in the liver accompanied by increased plasma insulin and glucagon like peptide-1 (GLP-1). ( 18 ) In the same previous report, we found GLP-1 antagonist Exendin (9-39) canceled AMPK phosphorylation. Furthermore, it is reported that secretion of GLP-1 has the rhythm and its secretion level in the active-phase is higher than that in the rest-phase.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Recently, we have demonstrated that a single oral administration of CLPr at ZT3 also increased phosphorylation of AMPK and LKB1 in the liver accompanied by increased plasma insulin and glucagon like peptide-1 (GLP-1). ( 18 ) In the same previous report, we found GLP-1 antagonist Exendin (9-39) canceled AMPK phosphorylation. Furthermore, it is reported that secretion of GLP-1 has the rhythm and its secretion level in the active-phase is higher than that in the rest-phase.…”
Section: Discussionsupporting
confidence: 70%
“…(17) Moreover, the results from our more recent report demonstrate that an antagonist for GLP-1 receptor Exendin (9-39) cancels CLPr-promoted AMPK phosphorylation. (18) In the same report, we have found that CLPr regulates the circadian clock gene expression through the GLP-1 signaling pathway. It is reported that AMPK down-regulates expression of Bmal1, which is one of the core clock genes.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Skipping breakfast and eating late at night can result in a shift of the circadian clock to nighttime, increasing the risk of obesity and diabetes ( 7 ). Various functional food components have been reported to contribute to the regulation of the circadian clock, for instance, caffeine ( 8 ), and flavonoids ( 9 , 10 ). Functional food components can contribute to the regulation of the circadian clock and are thought to have beneficial effects on health from a chrono-nutritional perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the daily light/dark cycle represents circadian rhythms’ primary synchronizer (‘zeitgeber’) [ 4 ]. However, certain nutrients have been reported to act as non-photic zeitgebers, such as caffeine [ 5 ] and dietary polyphenols [ 6 ]. The present review aims at providing evidence on the molecular bases of the role of dietary omega-3 (ω-3) fatty acids as non-photic zeitgebers.…”
Section: Introductionmentioning
confidence: 99%